DEEP STRUCTURE AND FORMATION MODEL OF CONTINENTAL CRUST OF THE VERKHOYANSK FOLD- AND-THRUST BELT IN THE LATE MESOZOIC - L. V. Kungurtsev; E. Y. Goshko (Геодинамика и тектонофизика, 2023)
The article considers the geological framework of a large orogenic structure in northeastern Eurasia - the Verkhoyansk fold-and-thrust belt (VFTB), formed in the Late Mesozoic on the eastern margin of the Siberian craton. Zoning of geopotential fields and the authors' interpretation of frequency-energetic characteristics along the 3-DV reference geo-physical profile provided the basis for modeling the deep structure of the VFTB and adjacent structures of the Siberian craton. There were identified structural zones of different geodynamic nature: the outer zone of the fold belt, underlain by the dropped margin of the craton; the inner zone of the VFTB with the oceanic crust at the base; the rear-zone structures formed by the Verkhoyansk complex in the subduction zone of the Uyandina-Yasachnaya island arc. In the Earth's crust of the VFTB there are distinguished two layers of approximately equal thickness: the lower one comprises a duplex system of complexes of the oceanic crust, and the upper one is built up by formations of the Verkhoyansk terrigenous complex, which have also undergone folding and duplexing. In parallel with thrusting of the upper terrigenous layer over the craton in the zone of collision between the VFTB structures and the Siberian craton margin there also occurred subduction of the lower layer of the VFTB under its margin. This led to an increase in thickness of the craton's crust by 5-10 km from below. The development of the Uyandina-Yasachnaya island arc system comprises two stages associated with blocking of the subduction zone and its transition towards the Oimyakon Ocean, which increased its area and complicated the structure. The paleosubduction zones and blocking structures are well-traced on the deep sections of reference seismic profiles.